Performance of Agricultural Wastes as A Biofilter Media for Low-Cost Greywater Treatment Technology - K. Abaas, Ebtesam; Atalah K. Ali, Seroor (Journal of Engineering and Sustainable Development, 2024)
Iraq currently faces an absence of water, worsened by population growth. As a result, if new water sources are not supplied, the country’s yearly per capita water supply will decrease. This study developed a simple, promising, and economical method for on-site greywater treatment, employing agricultural waste as a biofilter medium and irrigation water in rural Iraqi areas. Experiments were carried out in this study to evaluate the multimedia filter device’s efficacy in treating greywater. Three bioreactor columns were filled to the necessary height with various substrates—wood chipsBTF1, rice huskBTF2, and date palm fiberBTF3 at different operation conditions. The pollutant removal efficiency (Chemical Oxygen Demand, Total suspended solids, nitrate, and Phosphorous) for BTF1 was 61.6, 70.3, 45 and 42.45, for BTF2, it was 65.7, 43, 50.21%, and 55%. And for BTF3, it was 63.3, 75.6, 55, and 52.52, respectively. Rice husk is the most effective medium for eliminating pollutants, and using agricultural wastes as biofilter media could be a promising option for greywater treatment, especially in rural areas that lack sanitation services and produce a high amount of this waste annually.